Integration of geophysical applications in heterogeneous near-subsurface environments for archaeological investigations - Muhammad Taqiuddin Zakaria,; Nordiana Mohd Muztaza,; Ismail Ahmad Abir,; Nur Azwin Ismail,; Shyeh Sahibul Karamah Masnan, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Lembah Bujang is well-known for its cultural heritage, comprising a vast variety of archaeological structures and artifacts that could potentially offer valuable insights into the area’s historical timeline. However, identifying buried archaeological features via geophysical surveys is a complicated process that necessitates a comprehensive comprehension of both physical properties and archaeological knowledge. To overcome this challenge, a research project was conducted to detect clay brick structures using an integration of geophysical methods such as magnetic and 2-D resistivity at two separate locations within the SB2ZZ and SB2 sites. The research discovered two primary types of archaeological features for these areas, which are mound surfaces and scattered exposed clay bricks. The magnetic data was processed to identify potential clay bricks, which were then confirmed using 2-D resistivity. At the SB2ZZ site, excavations uncovered buried clay brick structures, which reinforced the interpretation of geophysical findings. Both SB2ZZ and SB2 sites demonstrated that clay bricks typically exhibit high magnetic anomalies and resistivity values ranging from 50-140 nT and 400-1000 Ωm, respectively. In conclusion, the combined use of geophysical methods in this study provided detailed subsurface images that were validated by excavation data.